# quick easy question im sure

• Jan 25th 2010, 06:01 PM
wonderd
quick easy question im sure
can someone explain to me how -y=-|x|+2 turns into y=|x|-2
• Jan 25th 2010, 06:02 PM
Sudharaka
Dear wonderd,

Multiply the whole equation by -1.
• Jan 25th 2010, 06:46 PM
wonderd
i dont understand, i do understand that to get the y by itself you divide by -1 but what are you suspose to do to the other side of the equal sign?
can someone explain how to divid -1 by -|x|+2 properly?
• Jan 25th 2010, 07:12 PM
fishcake
Quote:

Originally Posted by wonderd
i dont understand, i do understand that to get the y by itself you divide by -1 but what are you suspose to do to the other side of the equal sign?
can someone explain how to divid -1 by -|x|+2 properly?

You divide each of the terms by -1:

$\frac{-|x|}{-1} = |x|$

$\frac{2}{-1} = -2$

Thus, you end up with $|x|-2$.
• Jan 25th 2010, 07:41 PM
wonderd
thank you :)
• Jan 26th 2010, 03:43 AM
HallsofIvy
Or, as sudharaka said, multiply both sides of the equation by -1:
(-1)(-y)= (-1)(-|x|+ 2). The left is, of course, y and on the right you have (-1)(-|x|)+ (-1)(2)= |x|- 2.
• Jan 26th 2010, 04:50 AM
Quote:

Originally Posted by wonderd
can someone explain to me how -y=-|x|+2 turns into y=|x|-2

Hi wonderd,

you may add y to both sides

$-y=-|x|+2$

$y-y=y-|x|+2$

$0=y-|x|+2$

$|x|=y+|x|-|x|+2$
$|x|=y+2$
$|x|-2=y+2-2,\ |x|-2=y$